MENIMBANG CALON PERSEORANGAN DALAM PEMILU PRESIDEN - Prayudi Prayudi (Sekretariat Jenderal DPR RI, 2011)
One of a proposal constitution amendment initiative by The Council of Regional Representative (DPD’s) is about the independent candidate of presidential election. These proposal tend to reflect of public assessment over a parties role in the nomination every pairs of pre-candidate process before on the next stages become the candidate of President and Vice President definitive. The parties domination is not only presenting an impact of elite oligarchy and their particular interest impression, but also colored by an assumption on money politics transaction.